A new automated model brings stability to finite‐element simulations of capacitive deionization. Issue 6 (3rd November 2021) - Nordstrand, Johan; Dutta, Joydeep
Abstract: The massive need for freshwater is driving new desalination technologies such as capacitive deionization (CDI), wherein an applied electric field between porous electrodes removes salt ions from water. In this work, we present substantial advances in numerical approaches to 2D finite‐element models that make it possible to tractably and accurately simulate the local transport, charge‐transfer, and ion‐adsorption processes. This is achieved by introducing a new numerical approach that improves the stability of the method (SmD), which further allows precise and effective modeling that was previously too unstable for use in the state‐of‐the‐art 2D models. The results show that the model now accurately and reliably simulates CDI processes while being effectively applicable to a wider range of structural (device level) and operational conditions (like flow). Crucially, this opens up new opportunities that allow us to provide novel insights into the CDI processes, especially relating to ion‐starved conditions. Finally, novel algorithms support fully automatic implementation with simultaneous fit to multiple data sets and we openly provide all software code to increase accessibility. Thus, we fundamentally believe that the developed model will provide a solid foundation for 2D spatiotemporal simulations of capacitive deionization and aid the future development of CDI technology. Abstract : This work introduces the stabilized mD (SmD) model for describing desalination by capacitive deionization (CDI). Based on clever new algorithms, the model automatically tunes fitting parameters to dynamic data and predicts 2D dynamics. The enhanced stability enables detailed correction factors to simulations that would previously have crashed. Furthermore, the generalized framework permits smooth simulations of various structures and operations.